How to be a successful entrepreneur - Scaramucci, Anthony (Henry Stewart Talks, 2018)
Entrepreneurship, Self-identity, Risk and resilience, Management style, Delegation, Empowerment, Accountability, Enabling employees to learn from mistakes, Flexibility